Kebijakan Fiskal dalam Perspektif Ekonomi Islam - Dinda, Mita; Alrasyid, Farhan; Gunawan, Syahrul (Lembaga Yasin AlSys, 2023)
Fiscall policy' is a policy madel by thel government withl the aiml of regulatingl income and expenditure within the country in order to maintain stability and encourage economic growth.In islamic economics,fiscal policy is intended as one of the tools to create a goal according to sharia. The intended purpose of sharia is :maintaining the welfare and also ownership.According to islam,there are principles that must be adhered to in implementing fiscal policy according to sharia or according to islam.Among these principle of muamalah,namely where every muslim will be freed in therms of carrying out an activity or business activity that has been recommended in Islam.